1970
DOI: 10.1115/1.3449648
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Arrangement of Rectangular Fins on Horizontal Surfaces for Free-Convection Heat Transfer

Abstract: Experimental average heat-transfer coefficients for free-convection cooling of arrays of isothermal fins on horizontal surfaces over a wider range of spacings than previously available are reported. A simplified correlation is presented and a previously available correlation is questioned. An optimum arrangement for maximum heat transfer and a preliminary design method are suggested, including weight considerations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
83
1
1

Year Published

1971
1971
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(91 citation statements)
references
References 0 publications
6
83
1
1
Order By: Relevance
“…. In our investigation we find the value of Ra lies in the range of 10 6 . This conforms the flow set up due to density difference is in laminar zone.…”
Section: Effect Of Notch On Nusselt Numbermentioning
confidence: 51%
See 1 more Smart Citation
“…. In our investigation we find the value of Ra lies in the range of 10 6 . This conforms the flow set up due to density difference is in laminar zone.…”
Section: Effect Of Notch On Nusselt Numbermentioning
confidence: 51%
“…Rayleigh Number remains almost constant with increase in Nusselt Number for constant heat flux. Which gives the value of Rayleigh number gives in the order 10 6 .This shows the flow setup due to variation in density is laminar. The heat transfer coefficient is maximum in case of triangular (In the limit up to 20%) shape notch followed by trapezoidal (In the limit up to 20%) and Rectangular shaped notch (In the limit up to 20%) at constant heat flux due to effective removal of stagnant zone fin area.…”
Section: Discussionmentioning
confidence: 89%
“…In this case, the flow at the middle region of fin arrays is called as up-down flow (or sliding chimney flow). Jones and Smith [17] measured the effect of fin height and spacing on heat transfer coefficient. They found that the most important geometrical variable was fin spacing.…”
Section: Introductionmentioning
confidence: 99%
“…Refs. [21][22][23] are among the early works which have concentrated on horizontal rectangular fins in configurations heated from the bottom walls. The more recent studies include, for example, Ref.…”
Section: Introductionmentioning
confidence: 99%